MH370 crisis: the adequacy of the Malaysian Civil Aviation Act 1969 / Ainul Hafiza Zainudin ... [et al.] - Zainudin, Ainul Hafiza; Abu Bakar, Mardiah Hayati; Wan Rosli, Wan Rosalili; Abang Bolhil, Abang Ikhbal; Ibrahim, Farrah Shafeera (2014)
It has been close to three months since world was shocked by the disappearance of Malaysian Airline's flight MH370. Criticisms continue to zero in on Malaysia as to the manner its authorities are handling the situation, mismanaging the search and holding back information. This study aims to analyse the conundrums of crisis management practiced by Malaysia and investigate whether the Malaysian Civil Aviation Act 1969 under the purview of Malaysian Civil Aviation Department is an adequate regulatory framework to exercise regulatory functions in respect of civil aviation with reference to the International Standards and Recommended Practices set by International Civil Aviation Organization including the establishment of standards and their enforcement in context of a plane crash and the subsequent search for wreckage.